GALLBLADDER AND METHODS OF ITS EXAMINATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Diagnosis of the gallbladder and biliary tract is based primarily on the study of patients' complaints, anamnesis and the results of physical examination. Patients most often complain of the following: pain, dyspepsia, fever, chills, skin itching, jaundice. When determining the anamnesis, it is necessary to pay attention to whether the patient has previously had jaundice and acute diseases of the liver and gallbladder, attacks of colic, which may have triggered this disease of these organs (chronic cholecystitis, cholangitis and cholelithiasis)